2006
DOI: 10.1136/adc.2004.064477
|View full text |Cite
|
Sign up to set email alerts
|

The misdiagnosis of epilepsy in children admitted to a tertiary epilepsy centre with paroxysmal events

Abstract: Aims: To determine the proportion of children admitted with difficult to treat paroxysmal events to a tertiary epilepsy centre who did not have epilepsy. Methods: In an observational retrospective study, all case notes of 223 children admitted in 1997 were examined. The referral was made from the local paediatric department in 51% of cases, other departments in 27%, and from general or specialist practitioners in 22%. Doubt regarding the diagnosis of epilepsy was expressed in the referral note in 17%. On admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
160
1
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(176 citation statements)
references
References 14 publications
3
160
1
12
Order By: Relevance
“…The diagnosis of epilepsy is often difficult and misdiagnosis is common (Uldall, Alving, Hansen, Kibaek, & Buchholt, 2006). A review of misdiagnosis of epilepsy by Benbadis and by Chapman and the midline thalamic nuclei, in which it is relatively easy to create limbic seizures in kindling models as they are associated with an increased excitability in the neurons (ibid.).…”
Section: Misdiagnosismentioning
confidence: 99%
“…The diagnosis of epilepsy is often difficult and misdiagnosis is common (Uldall, Alving, Hansen, Kibaek, & Buchholt, 2006). A review of misdiagnosis of epilepsy by Benbadis and by Chapman and the midline thalamic nuclei, in which it is relatively easy to create limbic seizures in kindling models as they are associated with an increased excitability in the neurons (ibid.).…”
Section: Misdiagnosismentioning
confidence: 99%
“…The missense SNV in SCN4A is interesting as it is very rare (0.0012 minor allele frequency), inherited from a heterozygous parent, but made homozygous on the UPD chromosome, and located in a gene that encodes a subunit of a voltagegated sodium channel. This sodium channel is implicated in a diversity of neuromuscular disorders, such as periodic paralysis and myotonia congenita, diseases that mimic seizure disorders (Stephenson et al 2004;Uldall et al 2006). While channelopathies often follow a dominant mode of inheritance (Koch et al 1993), recessive modes have been seen as well (Trip et al 2008), and several channel proteins are known to underlie severe seizure disorders, such as KCNQ2 (Ohtahara syndrome) (Yamatogi and Ohtahara 2002) and paralogs of SCN4A, such as SCN1A (Wolff et al 2006), SCN2A (Kearney et al 2001), and SCN9A (Singh et al 2009).…”
Section: Identifying Plausibly Pathogenic Genetic Variation In the Ddmentioning
confidence: 99%
“…Several reports have described misdiagnosis of epilepsy. 2,3) Indeed, some studies have reported that 30-42% of patients initially thought to have epileptic seizures were later found to have convulsive syncope due to cardiovascular causes. 3,4) Many cardiovascular disorders may cause LOC complicated by abnormal movements attributable to general- ECG for 6 min before activation and 1 min after activation was stored in the ILR.…”
Section: Discussionmentioning
confidence: 99%